Analysis of parameters of purine metabolism in patients with diabetes mellitus type 2 - Chernyaeva, A.O.; Mykytyuk , M.R.; Karachentsev, Yu.I. (Medicni Perspektivi, 2023)
The aim of this research is to comprehensively analyze the current state of purine metabolism as well as assess its features in patients with diabetes mellitus type 2, taking into account the clinical and metabolic polymorphism of the disease. The authors examined 327 patients with diabetes mellitus type 2 (144 men and 183 women), a group of individuals with an average age of 57.8±10.1 years. The average duration of the disease was (9.3±7.3) years. All subjects received oral hypoglycemic therapy. The researchers determined anthropometric indicators, indicators of carbohydrate metabolism, concentration of creatinine, uric acid, parameters of the blood lipid spectrum, purine bases, activity of xanthine oxidase and hypoxanthine-guanine-phosphoribosyltransferase in the blood. In the course of the study the authors verified excretion of uric acid and creatinine renal uric acid, fractional clearance of uric acid, total tubular reabsorption of uric acid and coefficient of complete degradation of purine bases. Using the software complex "Statgraphics Centurion 18.0", we statistically analyzed the obtained data. The research showed that a decrease in assimilation, increased oxidation of purine bases due to the activation of xanthine oxidase, and a decrease in their reutilization by inhibiting the activity of hypoxanthine-guanine-phosphoribosyltransferase cause the high intensity of purine catabolism in patients with diabetes mellitus type 2. Hyperuricemia (28.0%), increased creatinine renal uric acid (62.3%), increased coefficient of complete degradation of purine bases (41.6%), activity of xanthine oxidase (38.8%) and inhibition of hypoxanthine-guanine-phosphoribosyltransferase activity (50.3%) dominate in the structure of disorders of purine bases in patients with diabetes mellitus type 2. We found that more than 50% of the subjects had high concentrations of purine bases in the blood. Purine bases concentrations in the blood of patients with diabetes mellitus type 2 closely correlate with each other and with the activity of xanthine oxidase and do not correlate with the level of uricemia, the level of uricemia does not correlate with the level of uric acid excretion. That is, the concentration of uric acid in the blood of patients with diabetes mellitus type 2 does not objectively reflect its production in the body. Patients with diabetes mellitus type 2 with obesity associate hyperuricemia with significantly lower creatinine renal uric acid and fractional clearance of uric acid as well as activation of the anabolic pathway of purine bases deposition.